Factors Influencing the Compliance of Person in Charge (PIC) In The Accreditation Documentation Management System at Pelita Insani Hospital - Karyono, Ferrita Aisya (Universitas Tribhuwana Tunggadewi, 2025)
To improve service quality, hospitals in Indonesia are required to undergo accreditation organized by SNARS. This process demands systematic documentation of patient care and service data. However, many documents are often not reported or recorded properly, which necessitates an effective management system. The Accreditation Documentation Management System (ADMS) is an IT-based tool designed to manage accreditation documents efficiently and is operated daily by the designated Person in Charge (PIC). At Pelita Insani Hospital, the use of ADMS for data reporting remains suboptimal due to several influencing factors. The purpose of this research was to examine the factors that influence the obedience of PIC at Pelita Insani Hospital. This research used cross sectional design. Population were all of the PIC at Pelita Insani Hospital, 150 persons. The sample were collected by proportional random sampling. The total sample of this research were 130 respondents. The dependent variable was the obedience. The data were collected by questionnaire and observation. The data were analized using multiple linear regression with significance level p 0,05. The result showed that there were influence between knowledge (p = 0,000), motivation (p = 0,000) and workload (p=0,043) toward the obedience of PIC to report data with Accreditation Document Management System however, facilities did not significantly influence the compliance of the Person in Charge (PIC) in reporting using the Accreditation Documentation Management System (p = 0.902). It can be conclude that there were significant effect of knowledge, motivation and workload toward the obedience of PIC to report the data with Accreditation Document Management System Based on these findings, hospital management is advised to enhance PICs’ knowledge, motivation, and manage their workload to improve compliance in ADMS reporting. Additionally, upgrading facilities and infrastructure may also support better reporting outcomes.